THE EFFECT OF MOTIVATION, WORK DISCIPLINE AND WORK EXPERIENCE ON THE PERFORMANCE OF STAFF AT PRIMA INDONESIA UNIVERSITY - Faris, Salman; Prasetya, Syauqi Ari (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
This study aims to determine the effect of Motivation, Work Discipline and Work Experience to Work Performance of UNPRI's staff by partially or simultaneously. This research are conducted to UNPRI's staff. The population in this research are the staff of UNPRI. Data collection methods in this study were questionnaires. The sampling technique used is the Random Sampling technique. Determination of the number of samples in this research using the Slovin formula with an error level of 5% so as to obtain a sample of 148 staff from the total population of 234 staff at UNPRI. Analysis prerequisite test uses validity, reliability test. Data analysis techniques using descriptive analysis, multiple correlation analysis, multiple regression analysis and coefficient of determination with calculations using SPSS version 20.0. Research results sourced from data processing show a positive relationship between the variables of Motivation, Work Discipline and Work Experience to Work Performance of UNPRI's Staff. From the analysis it was found that partially the influence of Motivation, Work Discipline and Work Experience to Work Performance of UNPRI's Staff each amounted to 13,8%; 9,7% dan 15,4%. Simultaneously the effect of Motivation, Work Discipline and Work Experience on the performance of UNPRI's Staff was 38.90% and the rest was influenced by other variables not proposed in this study.